Beauty growth-mindset promotes prosocial and altruistic behavior - Hung, Iris W. (2024)
Funding Information: Funding was provided by the Chinese University of Hong Kong, Shenzhen (Grant No. UDF01002194), Funda\u00E7\u00E3o para a Ci\u00EAncia e a Tecnologia (Grant Nos. UID/ECO/00124/2013, UID/ECO/00124/2019 and Social Sciences DataLab, LISBOA-01-0145-FEDER-022209), POR Lisboa (Grant Nos. LISBOA-01-0145-FEDER-007722, LISBOA-01-0145-FEDER-022209) and POR Norte (Grant No. LISBOA-01-0145-FEDER-022209). Publisher Copyright: © The Author(s) 2024.